2019
DOI: 10.1038/s41586-018-0823-6
|View full text |Cite
|
Sign up to set email alerts
|

A wireless closed-loop system for optogenetic peripheral neuromodulation

Abstract: Summary Paragraph The fast-growing field of bioelectronic medicine aims to develop engineered systems that relieve clinical conditions through stimulation of the peripheral nervous system (PNS) 1 – 5 . Technologies of this type rely largely on electrical stimulation to provide neuromodulation of organ function or pain. One example is sacral nerve stimulation to treat overactive bladder, urinary incontinence and interstitial cystitis/bladder pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
374
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(374 citation statements)
references
References 38 publications
0
374
0
Order By: Relevance
“…37 On the other extreme, centimetre-sized light sources would be beneficial for delivering homogenous illumination to entire organs in vivo, e.g., for optogenetic control of bladder function. 38 OLEDs can also be stacked on top of each other, 39 to enable co-localized multi-colour optogenetic excitation. Further, they can made transparent, 40 which allows for simultaneous imaging through the light source.…”
Section: Discussionmentioning
confidence: 99%
“…37 On the other extreme, centimetre-sized light sources would be beneficial for delivering homogenous illumination to entire organs in vivo, e.g., for optogenetic control of bladder function. 38 OLEDs can also be stacked on top of each other, 39 to enable co-localized multi-colour optogenetic excitation. Further, they can made transparent, 40 which allows for simultaneous imaging through the light source.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other promising and more rapidly hydrolyzable PEG/IL-2 conjugates (e.g. NKTR-214 36 ), these findings are encouraging and could lead to future integration with wearable or implanted lightdelivery devices [37][38][39][40][41] which modulate drug activation. Consistent with other PEGylated cytokines, 36 we found that bioinspired, polymer-induced latency was able to prolong scIL-12 plasma circulation approximately 16-fold, potentially precluding the need for frequent, high dosing and improving tissue drug exposure in treatment settings.…”
Section: P R E P R I N T C O P Ymentioning
confidence: 90%
“…In the early days of optogenetics, research was conducted to activate neurons in the brain, but recently its applications have been extended to the heart, bladder, and other tissues as well as the brain . Representatively, Mickle et al used resistive strain sensors to monitor bladder functions in real time and adopted optogenetic techniques for peripheral neuromodulation in the bladder via μLED . They reported that the optogenetic technique of applying light to neurons helped the bladder function normally.…”
Section: Advanced Applications Of Smart Sensing Systems Based On Optomentioning
confidence: 99%